Potencial Biotecnológico dos microrganismos endofíticos isolados de plantas de jambu (Acmella ciliata (Kunth) Cass.) para controle de microrganismos patógenos - Ojeda, Cinthya Paola Ortiz (2017)
The Amazon rainforest has great biodiversity of species, including animals, plants and microorganisms. Many of these microorganisms are not yet known, as well as some of the potential uses and properties of these. Among these are the endophytic microorganisms who live inside the plants, many of them showing the same properties of the host. The plant “jambu” Acmella ciliata is known for its antimicrobial, antifungal properties among others, and is used in food and natural medicine in the Amazon region. For the isolation of endophytes, first held low-level disinfection of the twigs and leaves of the plant Acmella ciliata, sow and incubate the pieces of this plant material during 15 days at 28ºc. The isolated microorganisms were evaluated in trials of antagonism (Fusarium decemcellulare and Colletotrichum gloeosporioides) and antimicrobial activity (Streptococcus pyogenes and Candida parapsilosis). A total of 104 were isolated endophytic microorganisms (bacteria, filamentous fungi and yeasts), of this universe, 22 filamentous fungi and 16 bacteria showed inhibition of growth of plant pathogens, and six bacteria showed antimicrobial activity for Streptococcus pyogenes and Candida parapsilosis. Was shown that the endophytic microorganisms isolated from plant Acmella ciliata produce metabolites with antimicrobial and antifungal activity.